2016
DOI: 10.1039/c6ra07515k
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient synthesis of primary amides via aldoximes rearrangement in water under air atmosphere catalyzed by an ionic ruthenium pincer complex

Abstract: An ionic Ru pincer complex was demonstrated to be highly efficient catalyst for conversion of aldoximes and aldehydes into corresponding primary amides with environmental benignity, operational convenience and catalytic loading as low as 0.5 mol%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 49 publications
0
10
0
1
Order By: Relevance
“…In this line, Hao and Song describe a protocol to obtain primary amides under mild conditions . This strategy consists in the rearrangement of aldoximes promoted by NNN–Ru pincer complex 101 (Scheme ).…”
Section: Cross‐coupling Reactionsmentioning
confidence: 99%
“…In this line, Hao and Song describe a protocol to obtain primary amides under mild conditions . This strategy consists in the rearrangement of aldoximes promoted by NNN–Ru pincer complex 101 (Scheme ).…”
Section: Cross‐coupling Reactionsmentioning
confidence: 99%
“…Arene–ruthenium(II) complexes were also proved to be appropriate catalysts for the rearrangement of aldoximes generated in situ from the corresponding aldehydes. Recently, Song and co‐workers described a complexed ionic ruthenium pincer catalyst was applicable for the synthesis of amides from aldoximes . Nevertheless, compared with the rapid development of ruthenium catalyst, there existed few reports on the rearrangement of aldoximes utilizing rhodium catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…developed a series of ionic ruthenium complexes and found that tridentate complex 65 showed high catalytic activity for the rearrangement of aldoximes into primary amides under mild conditions (Scheme a). This reaction proceeded in water at 110 °C for 12 h . A range of aromatic, heteroaromatic, and conjugated aldoximes were found to be suitable substrates for this transformation, thereby giving the desired amides in good‐to‐high yields with excellent functional‐group compatibility.…”
Section: Synthesis Of Amides From Oximesmentioning
confidence: 99%